Attitudes and Barriers to Evidence-Based Practice in Optometry Educators. Issue 4 (April 2015) - Suttle, Catherine M.; Challinor, Kirsten L.; Thompson, Rachel E.; Pesudovs, Konrad; Togher, Leanne; Chiavaroli, Neville; Lee, Adrian; Junghans, Barbara; Stapleton, Fiona; Watt, Kathleen; Jalbert, Isabelle
ABSTRACT Purpose Evidence-based practice (EBP) is an essential component of good quality, patient-centered health care. This requires practitioners to acquire EBP skills and knowledge during undergraduate and continuing education. Evidence-based practice education exists in a range of health care disciplines, including optometry. Evidence-based practice education, however, depends on relevant skills and knowledge in educators. Courses and workshops exist for the development of EBP teaching skills in some areas of health care but not in optometry. Here, we describe a pilot workshop designed to enhance the teaching of EBP and to investigate the perspectives of optometric educators on EBP including their attitudes and perceived barriers to EBP and its teaching. Methods Twenty-seven optometric educators including 8 facilitators participated. Of these, 14 were academics (including the 8 facilitators) and 13 were practitioners. Evidence-based practice attitudes were assessed using the Evidence-Based Practice Attitude Scale-50 with appropriate modifications for optometry. Workshop design incorporated strategies to trigger discussion among participants. A nominal group technique was used to identify, prioritize, and reach consensus on barriers to EBP. Results Although some participants expressed reservations about EBP, a common understanding of the contemporary definition of EBP emerged in educators. Thirty-five barriers to EBP were identified; "time" was selected in the top five barriers by most participants and attracted the highest total score, well above any other barrier (negative attitude to EBP, volume of evidence, integration with clinical practice, and lack of lifelong learning mind-set). Attitudes toward EBP were generally positive and negatively correlated with age and time since graduation, respectively. Conclusions A group of optometrists and academics new to implementing education in EBP displayed positive attitudes to EBP but considered that its application and teaching could be significantly hindered by a lack of time to access and appraise the large volume of available research evidence in the field of eye care.